Future U.S. Security Relationships with Iraq and Afghanistan U.S. Air Force Roles - Thaler, David E. (RAND Corporation, 2008)
The authors describe possible regional security structures and bilateral U.S. relationships with Iraq and Afghanistan. They recommend that the United States offer a wide range of security cooperation activities to compatible future governments in Kabul and Baghdad but should also plan to hedge against less-favorable contingencies. They emphasize that the U.S. Air Force should expect to remain heavily tasked for the foreseeable future.